Intertemporal discoordination in the 100 percent reserve banking system - Romain Baeriswyl (Swiss National Bank, Study Center Gerzensee, 2014)
The 100%-Money Plan advocated by Fisher (1936) has a Misesian flavor as it aims at mitigating intertemporal discoordination by reducing (i) the discrepancy between investment and voluntary savings, and (ii) the manipulation of interest rates by monetary injections. Recent proposals to adopt the 100 percent reserve banking system, such as the Chicago Plan Revisited by Benes and Kumhof (2013) or the Limited Purpose Banking by Kotlikoff (2010), take, however, a fundamentally different attitude towards the role of the central bank in the credit market and ignore that intertemporal discoordination arises independently from whether the credit expansion is financed by the creation of outside or inside money. These plans allow the central bank to inject outside money into the credit market and to effectively lower interest rates in negative territory in order to overcome the limit that the liquidity trap sets to credit expansion in the fractional reserve system. Although such an attempt may succeed in stimulating the economy in the short run, it exacerbates intertemporal discoordination and weakens economic stability in the long run.
Keywords: E30; E42; E58; B53; 330; monetary systems; Chicago Plan; Austrian business cycles